A Multicenter Hospital Based Study on Prevalence of Lumbar Intervertebral Disc Herniation in Asymptomatic Individuals on MRI - Dr. Varun S.; Dr. Jishnu J.; Dr. Sahana S.; Dr. Bukke Ravindra Naik; Dr. V. Suresh Kumar (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Lumbar intervertebral disc herniation (LDH) is a common spinal disorder often associated with clinical symptoms such as low back pain and sciatica. However, recent studies have shown that a significant proportion of individuals with lumbar disc herniation remain asymptomatic. The role of magnetic resonance imaging (MRI) has become central in detecting these disc abnormalities, even in the absence of symptoms. Understanding the prevalence and characteristics of asymptomatic lumbar disc herniation can guide clinical decision-making and improve the management of patients presenting with back pain. Objective: This study aimed to assess the prevalence and types of lumbar intervertebral disc herniation and the degree of disc degeneration in asymptomatic individuals using MRI. The study also sought to evaluate the correlation between demographic factors and these abnormalities. Methods: A cross-sectional, hospital-based study was conducted over one year, including 200 asymptomatic individuals who underwent lumbar MRI for non-spinal conditions. Demographic data were collected, and MRI scans were analyzed for disc degeneration using the Pfirrmann grading system (Grades 1-5) and the presence of lumbar disc herniation, categorized as normal, bulge, protrusion, extrusion, or sequestration. Results: The prevalence of lumbar disc herniation in this asymptomatic population was 30%, with the majority of herniations occurring at the L4-L5 (40%) and L5-S1 (35%) levels. Disc bulge was the most common type of herniation (20%), followed by protrusion (7%). Extrusion and sequestration were rare (5% combined). Regarding disc degeneration, Grade 1 (normal) degeneration was observed in 55% of the cases, while Grade 4 (severe) degeneration was seen in 5%. The prevalence of herniation increased with age, particularly among individuals aged 40 and above (35% versus 25%). Conclusion: This study reinforces the concept that asymptomatic lumbar disc herniations are common and emphasizes the need for careful interpretation of MRI results in clinical practice. The findings underscore that disc abnormalities detected on imaging should be assessed in the context of symptoms, as many individuals with disc herniation may not require intervention.